Electronic Modulation and Built‐in Electric Field Strategies in Heterostructures Together Induce 1T‐Rich MoS2 Conversion for Advanced Sodium Storage - Hui Peng; Wenxing Miao; Jingtian Zeng; Zihao Wang; Chenhui Yan; Guofu Ma; Ziqiang Lei (Advanced Science)
Abstract 1T‐MoS2 is considered an attractive energy storage material due to its large layer spacing and excellent electrical conductivity. Unfortunately, 1T‐MoS2 is difficult to synthesize directly due to the substability, which limits its development and application. Electron‐filling engineering of Mo 4d orbitals is the core idea to induce an efficient conversion of 2H to 1T phase. Based on this theory, a homogeneous CuS@MoS2 heterogeneous nanosheet is successfully constructed based on electron‐rich CuS as an electron donor. Both density functional theory (DFT) and X‐ray absorption fine structure analysis (XAFS) illustrate that part of the electrons from Cu at the heterogeneous interface are transferred to Mo, which triggers the reorganization of Mo 4d orbitals and the formation of a strong built‐in electric field at the interface, and induces an irreversible phase transition from 2H to 1T in MoS2. Based on its structural features, CuS@MoS2 heterogeneous nanosheets have a high first discharge capacity of 725 mAh g−1 at 0.1 A g−1, excellent rate performance (466.73 mAh g−1 at 10 A g−1), and long cycle stability (506.03 mAh g−1 after 3200 cycles at 5 A g−1). This work provides new perspectives for the development of high‐performance sodium storage anode materials based on 1T‐rich MoS2.